In Vitro and In Silico Studies of Quinoline-2-Carbaldehyde Hydrazone Derivatives as Potent Antimicrobial Agents. (21st April 2022) - Celik, Ismail; Erol, Meryem; Puskullu, Mustafa Orhan; Uzunhisarcikli, Ebru; Ince, Ufuk; Kuyucuklu, Gulcan; Suzen, Sibel
Abstract: We previously synthesized a series of quinoline-2-carbaldehyde hydrazone derivatives and evaluated their antioxidant activities. In this study, the antimicrobial activities of these quinoline-2-carbaldehyde hydrazone derivatives were evaluated antimicrobial activity by the microdilution method, and there cytotoxic effect was investigated in MCF-7 and A549 cells by MTT assay. When the activity results were examined, although the antimicrobial activity of quinoline derivatives were equal or better than standard drugs in general, compound 4 (2 µg/mL) and 8 (1 µg/mL) against E. faecalis and 5 (8 µg/mL) against P. aeruginosa are the most effective derivatives of the series. Besides, disk diffusion test was applied to these three compounds, and significant zone formation was observed at 8 (7 mm) compared to vancomycin (9 mm). Compounds showed no antiproliferative in A549 and MCF-7 cell lines, and compound 4, 5, and 8, which showed the most effective antimicrobial activity, were examined in healthy cells (Beas-2b) and no effect on cell viability was found. To understand the mechanism of this action of these compounds against E. faecalis, molecular docking studies were performed on 15 different proteins, and it was concluded that the compounds interacted with FabH and not enough with other protein structures. The theoretical ADME profiles of compounds comply with Lipinski and other limiting rules. Also, some theoretical quantum parameters (HOMO-LUMO) of compounds, and both MEP analysis and geometric optimization analysis of 8 were calculated with 6–311 G (d, p) base set and DFT/B3LYP theory, and the results were shown. Graphical Abstract: